PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS MELALUI CONTEXTUAL TEACHING LEARNING (CTL) DI KELAS VIII SMP 44 SIJUNJUNG - Dian Febrinal (STKIP Pesisir Selatan, 2016)
The purpose of this study was to determine the increased activity of student learning and mathematical communication after applying contextual approach (CTL). This research is a classroom action research (PTK) conducted three cycles. Each cycle consists of four stages: planning, action, observation, and reflection. VIIIl subjects were students enrolled in the 2nd half of the school year 2015/2016 the number of students 17 The data in this study were collected through observation sheets and test mathematical communication skills. Data analysis technique used is deskiptifs analysis results showed that learning with contextual approach to the material can Circles menin mathematical communication activity and Capacity of students in class VIII SMPN 44 Sijunjung. Student activity records the results of group discussions make conclusions and conduct relevant activities reached the category of excellent, student activity noted the important essence of learning materials asking questions to the teacher asked to give an explanation to a friend in the study group in presenting the results of focus group discussions reaching both categories Activities answered questions students respond to teachers to respond and investigate student activity worksheets read watch on finding solutions achieve better value category. The average value obtained mathematical communication test is 81,15 with the percentase of completeness reach 82%